2000
DOI: 10.1037/0894-4105.14.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Verbal pragmatics following unilateral stroke: Emotional content and valence.

Abstract: Verbal pragmatic aspects of discourse production were examined in 16 right brain-damaged (RBD), 16 left brain-damaged (LBD), and 16 normal control right-handed adults. The facilitation effect of emotional content, valence hypothesis, and relationship between pragmatics and emotion were evaluated. Participants produced monologues while recollecting emotional and nonemotional experiences. Transcribed monologues were rated for appropriateness on 6 pragmatic features: conciseness, lexical selection, quantity, rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 57 publications
0
28
0
1
Order By: Relevance
“…Therefore, the extent to which emotion is expressed verbally by the RBD participants may be suppressed in response to negative, but not to positive, personal experience discourse topics-this provides some support for the valence hypothesis. Contrary to this finding, positive narratives produced by individuals with RBD were rated as less pragmatically appropriate (Borod et al, 2000) and reviews have demonstrated that evidence for the valence hypothesis has been restricted (Borod, 1993;Borod et al, 2002). Neuroimaging studies have also found limited support for this hypothesis and have concluded that the regions in the brain involved in emotional processing are more complex and specific than previously thought (Wager et al, 2003).…”
Section: Amount Of Appraisalmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, the extent to which emotion is expressed verbally by the RBD participants may be suppressed in response to negative, but not to positive, personal experience discourse topics-this provides some support for the valence hypothesis. Contrary to this finding, positive narratives produced by individuals with RBD were rated as less pragmatically appropriate (Borod et al, 2000) and reviews have demonstrated that evidence for the valence hypothesis has been restricted (Borod, 1993;Borod et al, 2002). Neuroimaging studies have also found limited support for this hypothesis and have concluded that the regions in the brain involved in emotional processing are more complex and specific than previously thought (Wager et al, 2003).…”
Section: Amount Of Appraisalmentioning
confidence: 79%
“…Emotionally charged stimuli elicited oral narratives from these individuals that were judged as less relevant and less concise (Bloom, Borod, Obler, & Gerstman, 1993) contained more embellishments, personalisations, and clarity disruptors (Gardner, Brownell, Wapner, & Michelow, 1983;Wechsler, 1973). It has also been observed that emotional content suppressed the pragmatic performance (e.g., conciseness, quantity, relevancy) of the RBD group, and that emotionally positive discourse topics elicited poorer performance (Bloom et al, 1993;Borod et al, 2000). Individuals with RBD made little use of affective information to integrate information across sentence boundaries (Brownell, Blum, & Winner, 1994).…”
Section: Emotion and Right Brain Damage (Rbd)mentioning
confidence: 92%
“…Given the selective emotional anomia found in these subjects, it appears unlikely that their impairment resulted from a general defect in recognizing the emotion, or a general defect in naming ability (although it should be noted that processing emotional speech content indeed appears to rely more on the right than the left hemisphere (Borod et al, , 2000. Instead, it is plausible that these patients suffered from a disconnection between, on the one hand, information in right posterior cortices about the emotion shown in the face, and, on the other hand, the left hemisphere networks required for lexical retrieval of the name of the emotion.…”
Section: Lateralized Processing Of Emotionmentioning
confidence: 95%
“…The right hemisphere seems to be largely responsible for the processing and comprehension of negative emotions (Atchley, Ilardi, & Enloe, 2003;Borod et al, 2000). Individuals with damaged left hemispheres seem to experience depression as a result of awareness of impairment while patients with right-hemisphere damage tend to be less aware of their deficits and experience depression as a result of impaired social interactions (Lezak et al, 2004).…”
mentioning
confidence: 97%